Fruit characters in pistachio progenies - Vargas F.J.; Romero M.A. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Several nut traits (nut weight, kernel weight, shelling percentage, shell dehiscence percentage and kernel colour) were recorded during two years in 407 pistachio seedlings, derived from 15 crosses. For all the traits, significant differences between progenies were observed. Regarding nut and kernel weight, results from the families were similar. Four crosses, 'Batoury' x 'C', 'Mateur' x 'C', 'Batoury' x 'Nazar' and 'White Ouleimy' x 'M-502', stood out for their interest, while 'Larnaka' x 'B' gave seedlings with small nuts. In relation to the parents, 'Batoury' and 'White Ouleimy' (females) and 'C' (male) were promising, while 'B' (male) was undesirable. Regarding shelling percentage, 'Larnaka' x 'M-502' was outstanding, differences between families, although significant too, were reduced. In relation to the percentage of split nuts, 'Larnaka' x 'Nazar' stood out. As regards the intensity of the green colour of the kernels, the family 'Mateur' x 'M-38' stood out.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)